Avaliação clínica, laboratorial e anatomopatológica do sistema urinário de ovinos confinados com ou sem suplementação de cloreto de amônio - Santarosa, Bianca P. [UNESP]; Ferreira, Danilo O.L.; Rodrigues, Marcela M.P. [UNESP]; Dantas, Gabriela N. [UNESP]; Sacco, Soraya R. [UNESP]; Lopes, Raimundo Souza [UNESP]; Dias, Adriano [UNESP]; Gonçalves, Roberto C. [UNESP] (FapUNIFESP (SciELO), 2016)
The urinary acidification with ammonium chloride (AC) is an efficient preventive method for urolithiasis in sheep. The objectives of this study with feedlot sheep receiving concentrated diet with high protein content were (1) to verify the effect of diet on urolith formation and development of the disease, (2) to analyze the macroscopic and histopathological characteristics of the urinary system, and (3) to relate the clinical, laboratory and necropsy findings with the presence of uroliths. Sixty male sheep were used: AC group (n=40), 400mg/kg AC/day, orally treated for 42 consecutive days, and control group (n=20), untreated. Seven times were determined for sampling with a seven-day interval, totaling 56 days of feedlot. Small uroliths were found in the renal pelvis of five sheep in both groups. The most relevant microscopic renal lesions were vascular congestion and tubular necrosis. It was concluded that the highly concentrated diet caused renal injury in both groups, without changing the renal function, what was proven by laboratory tests of urea and creatinine. Ammonium chloride provided to the CA group did not prevent urolith formation, but reduced its prevalence in comparison with the control group. Sheep of the control group had increased kidney damage, which resulted in higher incidence of crystalluria and tubular necrosis induced by the consumption of a diet rich in grains.
Clinical, laboratory and anatomopathological evaluation of the urinary system of feedlot sheep with or without ammonium chloride supplementation
Keywords: Histopatholgy; Kidneys; Small ruminants; Urinary acidifiers; Urolithiasis